Relationship Marketing and Value Creation in a Business-to- Business Context: A Perspective of the Malaysian Retail Channel - Teng, Huey Jong (2010)
This study is about developing an effective marketing strategy for the trade development department in building a long-term relationship with their retail channel. Building on the theories of relationship marketing (RM) and empirical studies across other discipline such as business-tobusiness (B2B) marketing and organizational buying behavior, this study seeks to deepen the understanding of how effective management of a B2B relationship can gain competitive advantage for the manufacturers through value creation with their intermediaries, i.e. the retailers. Also, how RM can take on a broader and more strategic role for FMCGs when it comes to managing the relationship with trade partners. The approach taken is through discovering elements that are of high perceived value by the retail trade and their influence on relationship commitment and subsequently the behavioral intentions of the retailers. This allows the manufacturer to decide on effective resource allocation in building and maintaining a mutually beneficial partnership. A total of 123 face-to-face surveys were conducted with retailers among randomly selected set of grocery stores and coffee shops that sell cigarette, soft drinks and beer in the Klang Valley. Findings indicate that the realization of economic value positively influences commitment which also has a positive impact on behavioral intentions of retailers i.e. loyalty, cooperation, advocacy (word-of-mouth). However, does not clearly indicate that relational, product, interaction and information value has a significant impact on retailers’ commitment under the study. This suggests that retailers selling FMCG product may prefer a more transactional than a relational exchange with the manufacture and may require more investigation.